7q-3(3q+6)=7(6+q)

Simple and best practice solution for 7q-3(3q+6)=7(6+q) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7q-3(3q+6)=7(6+q) equation:



7q-3(3q+6)=7(6+q)
We move all terms to the left:
7q-3(3q+6)-(7(6+q))=0
We add all the numbers together, and all the variables
7q-3(3q+6)-(7(q+6))=0
We multiply parentheses
7q-9q-(7(q+6))-18=0
We calculate terms in parentheses: -(7(q+6)), so:
7(q+6)
We multiply parentheses
7q+42
Back to the equation:
-(7q+42)
We add all the numbers together, and all the variables
-2q-(7q+42)-18=0
We get rid of parentheses
-2q-7q-42-18=0
We add all the numbers together, and all the variables
-9q-60=0
We move all terms containing q to the left, all other terms to the right
-9q=60
q=60/-9
q=-6+2/3

See similar equations:

| x*x=1/81 | | 6(c-79)=84 | | b/10+59=63 | | 4f-29=43 | | 8(x+3)=10x+6 | | 6(y+5)=4y+42 | | 21-3t=18 | | 7r+2=86 | | x/3+9=22 | | 56=t/6+49 | | x=-0.9x^2+2.8x+2.4 | | x=8+2/3 | | 2/3+2x=1/3-3x | | 9=m+24/4 | | X+5y=52 | | 20x^2−x−12=0 | | 28=8n-20 | | 2x^2+20x+51=9 | | 17y+34=136 | | 5+4w=29 | | 40-x=37-2 | | 9(y-83)=72 | | c/4-3=2 | | 46=-5d+6 | | 9(y–83)=72 | | 2x/3=46 | | 6x-8/21=5x+5/14 | | 70=m/9+63 | | f/9-36=28 | | 2x+3(x+5)=10 | | |x-1|=|x-5| | | 5(w-81)=40 |

Equations solver categories